Asuhan Keperawatan Pada Pasien Post Operasi Tumor Left Scapular Region: Studi Kasus Di RSUD dr. Soeselo Kabupaten Tegal - Fatiyah Alya Salsabila; Ahmad Zakiudin (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Tumor Left Scapular Region is an abnormal tissue growth in the left scapular area that can cause pain, mobility disturbances, and decreased upper extremity function. The aim of writing this case study was to obtain a description of the implementation of nursing care for Ny. H with Post-Operative Tumor Left Scapular Region in Mawar 2 Ward, RSUD dr. Soeselo, Tegal Regency. The method used is a case study with a nursing process approach including assessment, nursing diagnosis, intervention, implementation, and evaluation conducted on February 8–9, 2026. The assessment results showed that the patient complained of pain in the post-operative wound of the left scapula with a pain scale of 5, there was a risk of infection due to the operative wound, and the patient lacked knowledge about the disease experienced. Nursing diagnoses established were acute pain, risk of infection, and knowledge deficit. After nursing actions were carried out for 2×24 hours, pain decreased, no signs of infection were found in the operative wound, and patient knowledge increased. It can be concluded that the application of nursing care in patients with Tumor Left Scapular Region was able to help reduce pain, prevent infection, and increase patient knowledge to support the healing process optimally.